Students’ Interest and Persistence in Physics Education Programs: A Case Study at Indraprasta PGRI University - Ferry Mochammad Ichsan; Islami Dini Hidayati; Reza Ega Nugroho (Yayasan Darussalam Bengkulu, 2024)
The declining interest of students in physics education has become a major concern in many universities, as it influences persistence, motivation, and the future supply of qualified physics educators. This study aimed to investigate the reasons behind students’ decisions to enter and remain in the Physics Education Program at Universitas Indraprasta PGRI and to explore the extent of their interest in the field. Using a mixed-method descriptive approach, data were collected through questionnaires distributed via Google Forms to 18 participants out of a population of 30 students and analyzed qualitatively and quantitatively. The results revealed that 38% of students expressed strong interest in physics education, 42% reported limited interest, and 20% remained neutral, while factors such as family encouragement, peer influence, and lecturer support emerged as key determinants sustaining students’ persistence despite limited intrinsic motivation. The discussion indicates that student engagement in physics education is not merely shaped by individual passion for the discipline but is strongly reinforced by social and contextual factors that enable students to adapt and continue their studies. The implication of this research is that higher education institutions should develop strategic interventions, such as peer mentoring, family-inclusive support systems, and contextualized learning approaches, to strengthen student motivation and reduce attrition in physics education programs.